571. Safety and Immunogenicity of INO-4800, a COVID-19 DNA Vaccine as a Primary Series and Booster. (4th December 2021) - Tebas, Pablo; Agnes, Joseph; Giffear, Mary; Kraynyak, Kimberly A; Blackwood, Elliott; Amante, Dinah; Reuschel, Emma; Liu, Neiman; Purwar, Mansi; Christensen-Quick, Aaron; Andrade, Viviane M; Carter, Julie; et al.
Abstract: Background: DNA vaccines are safe, tolerable, elicit humoral and cellular responses, allow for repeated dosing over time, are thermostable at room temperature, and are easy to manufacture. We present a compilation of Phase 1 and Phase 2 data of Inovio's US COVID-19 DNA Vaccine (INO-4800) targeting the full-length Spike antigen of SARS-CoV-2. A South Korean Phase 2 study is ongoing. Methods: Participants in the open-label Phase 1 trial received 0.5 mg, 1.0 mg or 2.0 mg intradermally (ID) followed by electroporation (EP) at Days 0 and 28. An optional booster dose was administered >6 months post-dose 2. The Phase 2 further compared the 1.0 mg and 2.0 mg doses against placebo in a total of 401 participants randomized at a 3:3:1:1 ratio. ClinicalTrials.gov identifiers: NCT04336410 and NCT04642638 Results: The majority of adverse events (AEs) related to INO-4800 across both trials were mild in severity and did not increase in frequency with age and subsequent doses. In Phase 1, 78% (14/18) and 84% (16/19) of subjects generated neutralizing antibody responses with geometric mean titers (GMTs) of 17.4 (95%CI 8.3, 36.5) and 62.3 (95% CI 36.4, 106.7) in the 1.0 and 2.0 groups, respectively (Figure 1). By week 8, 74% (14/19) and 100% (19/19) subjects generated T cell responses by Th1- associated IFNγ ELISPOT assay . Following a booster dose, neutralizing GMTs rose to 82.2 (95% CI 38.2, 176.9) and 124.7 (95% CI 62.8, 247.7) in the 1.0 mg and 2.0 mg groups, respectively, demonstrating the ability of INO-4800 to boost (Figure 2). In Phase 2, neutralizing antibody responses demonstrated GMTs of 93.6 (95%CI 77.3, 113.4) in the 1.0 mg dose group and 150.6 (95%CI 123.8, 183.1) in the 2.0 mg dose group (Figure 3). Conclusion: INO-4800 appears safe and tolerable as a primary series and as a booster with the induction of both humoral and cellular immune responses. In addition to eliciting neutralizing antibodies, INO-4800 also induced T cell immune responses as demonstrated by IFNγ ELISpot. Finally, as a homologous booster, INO-4800, when administered 6-10.5 months following the primary series, resulted in an increased immune response without increase in reactogenicity. The 2.0 mg dose was selected for Phase 3 evaluation. Disclosures: Joseph Agnes, PhD, Inovio (Employee, Shareholder) Mary Giffear, BS, Inovio Pharmaceuticals, Inc. (Employee) Kimberly A. Kraynyak, PhD, Inovio Pharmaceuticals (Employee, Other Financial or Material Support, Stock options) Dinah Amante, BS, Inovio (Employee) Emma Reuschel, PhD, Inovio Pharmaceuticals (Employee) Aaron Christensen-Quick, PhD, Inovio Pharmaceuticals, Inc (Employee) Viviane M. Andrade, PhD, Inovio Pharmaceuticals Inc. (Employee) Gabriella Garufi, PhD, Inovio Pharmaceuticals, Inc. (Employee) Albert Sylvester, MS, Inovio (Employee, Shareholder) Matthew P. Morrow, PhD, Inovio Pharmaceuticals (Employee) Patrick P. Pezzoli, BS, Inovio Pharmaceuticals, Inc. (Employee) Jan Pawlicki, PhD, Inovio Pharmaceuticals (Employee) Elisabeth Gillespie, PhD, Inovio Pharmaceuticals, Inc. (Employee) Katherine Schultheis, MSc, Inovio Pharmaceuticals (Employee) Hedieh Badie, PhD, INOVIO Pharmaceuticals (Employee) Timothy A. Herring, MPH, Inovio Pharmaceuticals, Inc. (Employee, Other Financial or Material Support, Own stock in the company) Keiko O. Simon, PhD, Inovio Pharmaceuticals (Employee) Trevor R. F. Smith, PhD, Inovio (Employee, Shareholder) Stephanie Ramos, PhD, Inovio Pharmaceuticals (Employee) Jessica Lee, MPH, Inovio Pharmaceuticals (Employee) Michael Dallas, PhD, Inovio Pharmaceuticals, Inc. (Employee, Shareholder) Ami Shah Brown, PhD, Abbot Laboratories (Shareholder)IBB Biotech ETF (Shareholder)Inovio Pharmaceuticals (Employee)J & J (Shareholder)Moderna (Shareholder) Jacqueline E. Shea, PhD, Inovio Pharmaceuticals (Employee, Shareholder) J Joseph Kim, PhD, Inovio (Employee) David Weiner, PhD, Inovio (Board Member, Grant/Research Support, Shareholder, I serve on the SAB in addition to the above activities) Kate Broderick, PhD, Inovio (Employee) Trevor McMullan, MSc, Inovio (Shareholder) Jean Boyer, PhD, Inovio (Employee) Laurent Humeau, PhD, Inovio Pharmaceuticals (Employee) Mammen P. Mammen Jr., MD, Inovio Pharmaceuticals (Employee)